Repeatability of upper limb kinematics for children with and without cerebral palsy - Reid, S.; Elliott, Catherine; Alderson, J.; Lloyd, D.; Elliott, B. (Elsevier BV, 2010)
Background: There is increasing demand for a standardised and reliable protocol for the objective assessment of upper limb motion in clinical populations. This paper describes the repeatability of a three-dimensional (3D) kinematic model and protocol to assess upper limb movement for children with and without cerebral palsy (CP). Methods: Ten typically developing (TD) children (m=10.5   years±1.18) (m=10.5   years±1.18) and seven children with CP (spastic hemiplegia) (m=11.14   years±1.86) (m=11.14   years±1.86) completed upper limb motion analysis on two occasions separated by at least one week. Participants performed three trials of four functional tasks, where 3D joint angles were calculated at the thorax, shoulder, elbow and wrist. Within and between-day repeatability was assessed using coefficients of multiple determination (CMD).Findings: There were distinct kinematic patterns for both groups for each functional task. In relation to their peers, children with CP consistently displayed reduced elbow extension, and compensatory patterns at the shoulder and thorax. High within and between-day CMD scores were revealed for specific rotations, with the highest being obtained at joints with large ranges of motion. Interpretation: The chosen tasks delineate the upper limb kinematic patterns of those with and without CP. The model has high within and between-day repeatability particularly where joint rotations demonstrate a large range of movement. 3D motion analysis is a feasible assessment tool for use with clinical populations.